Distribusi Yang Tak Merata: Refleksi Teoretis Dan Empiris Dari Studi Literatur Ekonomi - Sahla Adnin Karimah; Nova Gita Lestari; Muhammad Farhan Al-muzhaffar (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to explore the phenomenon of unequal distribution of income and goods through a literature review approach. Using a qualitative method, the research analyzes a variety of scholarly sources including journals, books, and international institutional reports to understand the root causes and consequences of inequality in both global and national economic contexts. The findings reveal that unequal distribution is not solely the result of imperfect market mechanisms, but also stems from structural economic imbalances, global corporate dominance, unequal access to education, digital divides, and non-inclusive fiscal policies. Two major theoretical frameworks John Rawls’s theory of distributive justice and the structural inequality theory from the Neo-Marxian approach offer comprehensive insights into the need for systemic reform. This study emphasizes that inequality is not merely an economic issue, but also a moral and social challenge that must be addressed collectively by states, civil society, and international institutions.